Prevalence and severity of dental caries in school children in Saudi Arabia: A nationwide cross-sectional study - Saud M. Orfali; Ali S. Alrumikhan; Nader A. Assal; Adel M. Alrusayes; Zuhair S. Natto (Saudi Dental Journal)
Aim: This nationwide study assessed the prevalence and severity of dental caries in 6-, 12-, and 15-year-old school children across Saudi Arabia. This study examined differences between genders and among regions regarding the mean values of decayed, missing, and filled teeth (dmft/DMFT), the care index (CI), and the significant caries index (SiC index). Materials and methods: Data from 19,870 participants, 10,435 males and 9435 females, were collected using stratified multistage cluster random sampling. The survey team divided Saudi Arabia into five regions (northern, eastern, western, southern, and middle). To represent each respective region, a large city, two random towns (peri-urban), and four random rural areas were selected for surveying. Lastly, the sampling technique was applied by choosing random schools and random classes within the selected schools. Dental caries were assessed using the dmft/DMFT score, CI, and the top 30% and 10% of the sample dmft/DMFT scores (SiC30 and SiC10, respectively). Results: The overall prevalence of caries was 65.6%, with 72.1 occurring in primary teeth and 61.7% in permanent teeth. The percentages of individuals with missing teeth and filled teeth were 9.0% and 20.5%, respectively. The mean dmft was 3.93 ± 3.60, while the mean DMFT was 2.42 ± 2.52; most of the DMFT components were significantly higher in females than males, while the dmft components were higher in males. The northern region had the highest and worst DMFT/dmft ratios of the five regions. The mean SiC30 and SiC10 values were significantly higher than the overall average DMFT/dmft values (P < 0.001). Conclusion: Dental caries remain a public health challenge among school children in Saudi Arabia. The SiC and CI analysis indicated that caries management had a high overall efficacy, but that certain groups of the population may need targeted management in the future.